Nonlinear feedforward enabling quantum computation - Atsushi Sakaguchi; Shunya Konno; Fumiya Hanamura; Warit Asavanant; Kan Takase; Hisashi Ogawa; Petr Marek; Radim Filip; Jun-ichi Yoshikawa; Elanor Huntington; Hidehiro Yonezawa; Akira Furusawa (Nature Communications, 2023)
Abstract Measurement-based quantum computation with optical time-domain multiplexing is a promising method to realize a quantum computer from the viewpoint of scalability. Fault tolerance and universality are also realizable by preparing appropriate resource quantum states and electro-optical feedforward that is altered based on measurement results. While linear feedforward has been realized and become a common experimental technique, nonlinear feedforward was unrealized until now. In this paper, we demonstrate that a fast and flexible nonlinear feedforward realizes the essential measurement required for fault-tolerant and universal quantum computation. Using non-Gaussian ancillary states, we observed 10% reduction of the measurement excess noise relative to classical vacuum ancilla.